Mapteng ja biag (a beautiful life): A study on the child-rearing practices of farmers amidst agricultural shift in Bahong’s farms - Licos, Jennina A.; Roque, Ruth; Guazon, Hector (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology; Vol 1 No 2 (2023): The Flow of Things and Bodies: The Production of Flowers in La Trinidad, Benguet, 2025)
This paper focuses on the child-rearing practices and how they correspond with the shifting source of livelihood of the actors in Sitio Central Bahong, La Trinidad, Benguet, covering the themes of their nutritional diet, way of discipline, and parental aspirations.